The Effect of Corporate Governance on Firm Value in IICD Award Recipient Companies - Rizky Fadillah Nanda; Cacik Rut Damayanti (Pendidikan Administrasi Perkantoran, Universitas Negeri Makassar, 2021)
This study aims to examine and analyse the effect of corporate governance on firm value. Corporate governance is measured through institutional ownership, managerial ownership, the proportion of independent commissioners, the size of the board of commissioners, the female board of commissioners, the size of the board of directors and the size of the audit committee as independent variables, while firm value is measured by Tobin's Q as the dependent variable. The population in this study were IICD award-winning companies in 2014-2019 and obtained 12 companies as samples by purposive sampling using multiple linear regression data analysis techniques with SPSS 20. The results of the study simultaneously show that institutional ownership, managerial ownership, the proportion of independent commissioners, the size of the board of commissioners, the presence of female commissioners, the size of the board and the size of the audit committee have an effect on firm value.